The Dynamics of Forearc – Back‐Arc Basin Subsidence: Numerical Models and Observations From Mediterranean Subduction Zones. Issue 5 (17th May 2022) - Balázs, A.; Faccenna, C.; Gerya, T.; Ueda, K.; Funiciello, F.
Abstract: The subsidence history of forearc and back‐arc basins reflects the relationship between subduction kinematics, mantle dynamics, magmatism, crustal tectonics, and surface processes. The distinct contributions of these processes to the topography variations of active margins during subduction initiation, oceanic subduction, and collision are less understood. We ran 2D elasto‐visco‐plastic numerical models including surface and hydration processes. The models show the evolution of wedge‐top and retro‐forearc basins on the continental overriding plate, separated by a forearc high. They are affected by repeated compression and extension phases. Compression‐induced subsidence is recorded in the syncline structure of the retro‐forearc basin from the onset of subduction. The 2–4 km upper plate negative residual topography is produced by the gradually steepening slab, which drags down the upper plate. Trench retreat leads to slab unbending and decreasing slab dip angle that leads to upper plate trench‐ward tilting. Back‐arc basins are either formed along inherited weak zones at a large distance from the arc or are created above the hydrated mantle wedge originating from arc rifting. Back‐arc subsidence is primarily governed by crustal thinning that is controlled by slab roll‐back and supported by the underlying mantle convection. High subduction and mantle convection velocities result in large wavelength negative dynamic topography. Collision and continental subduction are linked to the uplift of the forearc basins; however, the back‐arc records ongoing extension during a soft collision. During the hard collision, both the forearc and back‐arc basins are ultimately affected by the compression. Our modeling results provide insights into the evolution of Mediterranean subduction zones. Plain Language Summary: In this study, we assess the physical and thermal parameters of the interior of our planet Earth by comparing the topographic variations, that is, subsidence and uplift patterns of high‐resolution numerical models and observations from the Mediterranean region of Europe. We particularly focus on subduction zones. These noteworthy regions experience the sinking of dense oceanic tectonic plates beneath less dense upper plates and are characterized by distinct uplift and subsidence patterns. Understanding these processes is important for evaluating seismic risk, but these regions also host important geo‐resources, including geothermal energy. Key Points: Evolution of forearc basins controlled by slab advance and steepening Subsidence of back‐arc basins controlled by slab roll‐back and mantle flow Insights into the evolution of Mediterranean forearc and back‐arc basin systems